Isolation and Identification of Type F Bovine Enterovirus from Clinical Cattle with Diarrhoea - Chengyuan Ji (MDPI AG, 2021)
Recently, bovine enterovirus (BEV) has caused several respiratory and gastrointestinal diseases outbreaks in cattle. Monitoring the epidemiological and pathogenic characteristics of this virus is crucial to controlling its spread. We isolated a BEV strain with typical cytopathic effects from the faeces of cows with significant diarrhoeal symptoms in China and observed the viral particles within 20–30 nm through transmission electron microscopy. Then, we designated this strain as HB19-1 in this study. The multistep growth curves showed that the virus propagated well in the MDBK cells. Molecular genetic analysis of VP1 indicated that HB19-1 belonged to the BEV-F1 group. Although the challenged ICR mice did not exhibit typical disease symptoms in animal infection assay, we observed significant pathological damage in the lungs, intestines, and muscle tissues. In summary, we isolated a BEV strain HB19-1 causing severe diarrhoea in cattle and proposed reinforcing the epidemiological surveillance of this virus.